Effect of Agronomic Intervention on the Productivity of Khadin Cultivated Rabi Crops in Arid Region for Enhancing Farm Income: A Case Study from Jodhpur (Rajasthan, India): RESEARCH PAPER - Kumawat, Ram Narayan; Santra, Priyabrata; Kumar, Mahesh; Nangia, Vinay; Devkota, Mina; Kumar, Dinesh (Annals of Arid Zone, 2025)
Khadin is a type of runoff farming system practiced in Indian Thar desert ensured cultivation of at least one crop in a year in the annual rainfall zone of 200 mm. Selection of better remunerative crop and provision of supplementary irrigation from collected rainwater considered important for improving farm income and water productivity (WP) in khadins. The specific objectives of present study were i) to develop facility for providing supplementary irrigations to test crops by using solar energy ii) to identify more remunerative crop under the prevailing conditions of khadins, iii) to find level of irrigation for higher water productivity, and iv) to validate research output through measurement of soil-water content and physiological characteristics of crops. In the study a water storage structure of 3.2 million litres constructed within khadin for collection of surplus runoff and it was lined with 300 micron HDPE sheet for creating supplementary irrigation facility. The three experimental crops mustard (Brassica juncea), barley (Hordeum vulgare) and gram (Cicer arietinum) were grown with three levels of supplementary irrigations to find out more remunerative crop. Standard methodologies were used to estimate soil-water content and physiological characteristics of crops. Results indicated that in khadin gram crop with supplemented irrigation recorded highest gram equivalent yield (GEY) of 2047 kg ha-1 which was 32 and 20% higher than barley and mustard, respectively. The highest economic water productivity (EWP) of Rs.122.54 m-3 was recorded with gram which had advantage of Rs 31.65 m-3 of water applied over barley. The provision of one supplementary irrigation to gram crop increased grain yield by 479 kg ha-1 and farm income by Rs. 28,740 ha-1 compared to farmer grown gram crop. The improvement of existing khadin system with a provision of supplementary irrigation at terminal crop growth stage and better crop selection increased the crop productivity and farm profit in semi-arid/arid areas of India.